TREATMENT OF DISEASES OF THE CARDIOVASCULAR SYSTEM IN CARDIOLOGY - Koziraximova Nargiza Kodirjonovna; Mavlonov Alisher Xasanovich (Journals Park Publishing, 2023)
This article provides a comprehensive overview of the contemporary approaches and advancements in the treatment of cardiovascular diseases within the field of cardiology. Through an analysis of current literature, we explore various methods ranging from traditional pharmacological interventions to cutting-edge interventional procedures. The review emphasizes the importance of a multidisciplinary approach, incorporating medications, lifestyle modifications, and innovative technologies to enhance patient outcomes.
Keywords: Cardiovascular diseases, cardiology, treatment, therapeutic advancements, interventional procedures, medications, lifestyle modifications.